Core-sheath composite fiber, method for producing the same, and fiber structure

CN116917560BActive Publication Date: 2026-10-30KURARAY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202280018535.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-03-04
Filing Date
2022-02-28
Publication Date
2026-10-30
Estimated Expiration
2042-02-28

AI Technical Summary

Technical Problem

[0004]已知熔融各向异性芳香族聚酯纤维具有高强力高弹性模量,但这些纤维的分子链沿着纤维轴方向高度取向,因此存在容易因磨损而发生原纤化的问题

Benefits of technology

[0058]根据本发明的芯鞘复合纤维,对于具有熔融各向异性芳香族聚酯作为芯成分且鞘成分为海岛结构的芯鞘复合纤维而言,可以得到即使在将鞘成分的岛部设为熔融各向异性芳香族聚酯并提高了其比例的情况下也能够通过使岛部微分散而抑制纺丝中的岛成分的凝聚、提高芯鞘复合纤维的耐原纤性、耐磨损性优异的纤维。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116917560B_ABST
    Figure CN116917560B_ABST
Patent Text Reader

Abstract

The present invention provides a core-sheath composite fiber, a method for producing the same, and a fiber structure. The core component (12) of the core-sheath composite fiber contains a melt-anisotropic aromatic polyester (A polymer), and the sheath component contains a bendable thermoplastic polymer (B polymer) and a melt-anisotropic aromatic polyester (C polymer). The sheath component has a sea component formed of the B polymer, an island component formed of the C polymer, and an island-in-sea structure in which a plurality of island portions (18) formed of the island component are dispersed in a sea portion (14) formed of the sea component.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Related applications

[0002] This application claims priority to Japanese Patent Application 2021-34707, filed on March 4, 2021, the entirety of which is incorporated herein by reference. Technical Field

[0003] This invention relates to a core-sheath composite fiber having melt-anisotropic aromatic polyester as the core component, improved fibrillation resistance, and excellent abrasion resistance, a method for manufacturing the same, and the fiber structure thereof. Background Technology

[0004] Melt-isotropic aromatic polyester fibers are known to possess high strength and high elastic modulus, but the molecular chains of these fibers are highly oriented along the fiber axis, thus making them prone to fibrillation due to wear. Therefore, a composite fiber has been proposed, which suppresses fibrillation by using molten anisotropic aromatic polyester as the core component and coating the surrounding area with a sheath component.

[0005] For example, Patent Document 1 (Japanese Patent Application Publication No. 2002-20932) discloses a composite fiber in which the core component is formed from melted anisotropic aromatic polyester (A) and the sheath component is formed from a flexible polyester (B) containing 0 to 10% of polymer (A), wherein the intrinsic viscosity [η] of the polyester (B) is 0.65 dl / g or more.

[0006] Patent document 1 describes a method of increasing the strength of the sheath component and simultaneously improving its adhesion to the core component by mixing the same polymer as the core component into the sheath component.

[0007] Patent document 2 (Japanese Patent Application Publication No. 2008-255535) discloses a core-sheath composite fiber that satisfies the following: the core component is formed from molten anisotropic aromatic polyester (polymer A), the sheath component has an island structure, and the sheath component ratio is 0.2 to 0.7; the island component constituting the sheath component is formed from a flexible thermoplastic polymer (polymer B), and the island component is formed from molten anisotropic aromatic polyester (polymer C); the island component ratio in the sheath component is 0 to 0.25; wherein, the composite fiber has 0.03 to 2.5% by mass of inorganic microparticles with silicate compounds as the main component attached to the fiber surface.

[0008] Patent document 2 describes that since the adhesion between the polymer without melt anisotropy and the melt anisotropy polyester is low and easy to peel off, a sheath component is formed by a mixture of melt anisotropy polyester and a polymer without melt anisotropy.

[0009] Existing technical documents

[0010] Patent documents

[0011] Patent Document 1: Japanese Patent Application Publication No. 2002-20932

[0012] Patent Document 2: Japanese Patent Application Publication No. 2008-255535 Summary of the Invention

[0013] The problem that the invention aims to solve

[0014] However, in Patent Document 1, when the proportion of molten anisotropic aromatic polyester in the sheath component exceeds 10%, unevenness will be generated on the fiber surface, resulting in poor spinnability. Therefore, the possibility of increasing the proportion of molten anisotropic aromatic polyester in the sheath component is denied.

[0015] Furthermore, regarding the composite fiber described in Patent Document 2, although it is stated that by attaching 0.03 to 2.5% by mass of inorganic microparticles with silicate compounds as the main component to the fiber surface, it is possible to suppress fiber adhesion and improve delamination, the fibrillation suppression of the fiber is only mentioned in relation to the significant improvement of fibrillation resistance and abrasion resistance by using a flexible thermoplastic polymer as the main component.

[0016] If molten anisotropic aromatic polyester can be used as the core component, and a large amount of molten anisotropic aromatic polyester can be mixed into the sheath component, which is coated with the surrounding core-sheath composite fibers, without impairing spinnability, then the adhesion between the core and sheath can be made stronger, sheath peeling can be suppressed, and higher abrasion resistance than before can be achieved. Furthermore, for the same reason, the sheath can be thinned, resulting in increased strength through the molten anisotropic aromatic polyester on the core side, which is therefore preferred.

[0017] Therefore, the object of the present invention is to provide a core-sheath composite fiber that increases the proportion of molten anisotropic aromatic polyester in the sheath component of the core-sheath composite fiber, suppresses fibrillation and deterioration of spinnability, and has excellent abrasion resistance.

[0018] Problem Solving Methods

[0019] In order to achieve the above-mentioned objectives, the inventors of the present invention conducted in-depth research and found that if, in a core-sheath composite fiber having molten anisotropic aromatic polyester as the core component, (I) the sheath component is set to an island structure having islands formed by molten anisotropic aromatic polyester, and the proportion of molten anisotropic aromatic polyester in the island structure is increased, sheath peeling can be prevented by improving the adhesion between the core and the sheath, further improving abrasion resistance, and the sheath can be thinned, and the strength can be improved by the molten anisotropic aromatic polyester of the core component. However, (II) on the other hand, it was noted that the spinning state deteriorated significantly due to the high proportion of molten anisotropic aromatic polyester, and the sheath component became fibrillated. Therefore, improving the spinning state and suppressing the fibrillation of the sheath component became new challenges. Furthermore, it was discovered that (III) by increasing the proportion of molten anisotropic aromatic polyester in the sheath component and drawing the extruded yarn produced by mixing the sheath component at a specific temperature with a specific draw value, the island portion formed by the molten anisotropic aromatic polyester can be micro-dispersed in the sea portion, thereby controlling the shape of the island portion. As a result, even when the proportion of molten anisotropic aromatic polyester in the sheath component is high, a good spinning state can be maintained, and fibrillation of the core-sheath composite fiber can be suppressed. Moreover, even when the sheath is thinned, abrasion resistance can be improved, thus completing the present invention.

[0020] That is, the present invention can be constructed in the following ways.

[0021] [Method 1]

[0022] A core-sheath composite fiber, wherein the core component comprises a molten anisotropic aromatic polyester (polymer A), and the sheath component comprises a flexible thermoplastic polymer (polymer B) and a molten anisotropic aromatic polyester (polymer C). The sheath component has an island structure where the polymer B forms a sea-like component, the polymer C forms an island-like component, and multiple islands formed by the island-like component are dispersed within a sea-like component.

[0023] The proportion of island components in the aforementioned sheath components exceeds 10% by weight, and,

[0024] In the cross-section obtained by cutting the core-sheath composite fiber along the fiber length direction, the maximum width W of the island portion having the largest width in the fiber perpendicular direction is 0.65 μm or less (preferably 0.60 μm or less, more preferably 0.55 μm or less, and even more preferably 0.50 μm or less).

[0025] In the island portion having the maximum width W described above, in the island portion that connects to the oblique line in the sheath component extending at an angle of 10° relative to the fiber length direction from one end to the other, the ratio L1 of the maximum length of the oblique length coinciding with the oblique line to the maximum width W of the island portion is 5.0 or more (preferably 5.1 or more, more preferably 5.2 or more, even more preferably 5.3 or more, even more preferably 5.5 or more).

[0026] [Method 2]

[0027] According to the core-sheath composite fiber of method 1, wherein...

[0028] The maximum length L1 of the aforementioned oblique length is 1.0 μm or more (preferably 1.3 μm or more, more preferably 1.5 μm or more, and even more preferably 1.7 μm or more).

[0029] [Method 3]

[0030] According to the core-sheath composite fiber described in method 1 or 2, wherein...

[0031] In the cross-section obtained by cutting the above-mentioned core-sheath composite fiber along the fiber length direction, the length L2 of the island portion of the sheath component in the fiber length direction is 450 to 1000 μm (preferably 500 to 800 μm, more preferably 550 to 650 μm).

[0032] [Method 4]

[0033] The core-sheath composite fiber according to any one of methods 1 to 3, wherein...

[0034] The thickness of the sheath component is 0.8 to 5.0 μm (preferably 0.9 to 4.0 μm, more preferably 0.9 to 3.8 μm).

[0035] [Method 5]

[0036] The core-sheath composite fiber according to any one of methods 1 to 4, wherein...

[0037] Polymer A and polymer C are the same type of melt-isotropic aromatic polyester.

[0038] [Method 6]

[0039] The core-sheath composite fiber according to any one of methods 1 to 5, wherein...

[0040] The core / sheath composition is 20 / 80 to 97 / 3 (preferably 50 / 50 to 96 / 4, more preferably 60 / 40 to 95 / 5, further preferably 70 / 30 to 94 / 6, even more preferably 75 / 25 to 93 / 7, particularly preferably 80 / 20 to 92 / 8, and most preferably 82.5 / 17.5 to 90 / 10), and the core / sheath composition is the weight ratio of the core composition to the sheath composition.

[0041] [Method 7]

[0042] The core-sheath composite fiber according to any one of methods 1 to 6, wherein...

[0043] The single filament fineness of the core-sheath composite fiber is 1-120 dtex (preferably 2-60 dtex, more preferably 2.5-30 dtex, and even more preferably 3-15 dtex).

[0044] [Method 8]

[0045] A method for manufacturing a core-sheath composite fiber, wherein the core component of the core-sheath composite fiber comprises a melt-anisotropic aromatic polyester (polymer A), and the sheath component comprises a flexible thermoplastic polymer (polymer B) and a melt-anisotropic aromatic polyester (polymer C). The sheath component has an island structure in which the polymer B forms a sea element, the polymer C forms an island element, and a plurality of islands formed by the island element are dispersed in a sea element formed by the sea element.

[0046] This method must at least have:

[0047] In the mixing process, a twin-screw extruder is used to mix the polymer B and polymer C used in the sheath component at a melting point (Mb)°C or higher relative to the melting point (Mc)°C of polymer B and a melting point (Mc-20)°C or higher but lower than (Mc)°C relative to the melting point (Mc)°C of polymer C. In addition, a different extruder than the twin-screw extruder used in the sheath component is used to melt and mix the polymer A used in the core component.

[0048] The extrusion process involves compounding and extruding the sheath and core components, which have been separately compounded in the mixing process, to obtain the discharged filament; and

[0049] In the extraction process, the ejected filament is extracted with a draw value of 13 to 50 (preferably 15 to 45, more preferably 16 to 40, further preferably 19 to 38, and particularly preferably 20 to 35), where the draw value is the ratio of the winding speed to the ejection speed.

[0050] [Method 9]

[0051] The method for manufacturing core-sheath composite fibers according to method 8 has the following characteristics:

[0052] The heat treatment process involves heat-treating the fibers obtained through the above-mentioned ejection process.

[0053] [Method 10]

[0054] A fiber structure comprising, in at least a portion, the core-sheath composite fiber described in any of embodiments 1 to 7.

[0055] In this specification, "the cross-section obtained by cutting the core-sheath composite fiber along its length" has the same meaning as the cross-section observed by cutting the core-sheath composite fiber with a plane encompassing the fiber length direction, and is hereby sometimes referred to as "fiber longitudinal section". Furthermore, the fiber perpendicular direction refers to the direction orthogonal to (or perpendicular to) the fiber length direction in the fiber longitudinal section.

[0056] It should be noted that any combination of at least two constituent elements disclosed in the claims and / or description and / or drawings is also included in this invention. In particular, any combination of two or more claims recited in the claims is also included in this invention.

[0057] The effects of the invention

[0058] According to the core-sheath composite fiber of the present invention, for a core-sheath composite fiber having a molten anisotropic aromatic polyester as the core component and a sheath component having an island structure, it is possible to obtain a fiber with excellent resistance to fibrils and abrasion resistance, even when the island portion of the sheath component is set as molten anisotropic aromatic polyester and its proportion is increased, the aggregation of the island component in spinning can be suppressed by micro-dispersing the island portion. Attached Figure Description

[0059] The invention will be more clearly understood by referring to the following description of preferred embodiments with reference to the accompanying drawings. However, the embodiments and drawings are for illustration and description only and should not be used to limit the scope of the invention. The scope of the invention is defined by the appended claims. In the drawings, the numbers of the same elements in the plurality of drawings denote the same parts.

[0060] Figure 1A This is a three-dimensional schematic diagram of a core-sheath composite fiber according to one embodiment of the present invention.

[0061] Figure 1B This is a schematic cross-sectional view observed when the core-sheath composite fiber is cut along its length.

[0062] Figure 2 This is an enlarged cross-sectional schematic diagram showing a portion of the sheath component of the core-sheath composite fiber.

[0063] Figure 3 This is a schematic cross-sectional view of the core-sheath composite fiber as observed when it is cut with a plane perpendicular to the fiber length direction.

[0064] Figure 4 This is a cross-sectional schematic diagram of the structure of the spinneret used in spinning the core-sheath composite fiber. Detailed Implementation

[0065] The present invention will now be described in detail based on examples. One aspect of the invention is a core-sheath composite fiber comprising a core component and a sheath component covering the core component, the sheath component having an island structure comprising sea and island components. The core component comprises a melt-anisotropic aromatic polyester (polymer A), and the sheath component comprises a flexible thermoplastic polymer (polymer B) and a melt-anisotropic aromatic polyester (polymer C), polymer B forming the sea component and polymer C forming the island component.

[0066] (Core components)

[0067] The molten anisotropic aromatic polyester (polymer A) used in the core component refers to a polymer that exhibits optical anisotropy (liquid crystal properties) in the molten phase. For example, by placing the sample on a heating stage, heating it in a nitrogen atmosphere, and observing the transmitted light of the sample, it can be determined whether it is a molten anisotropic aromatic polyester. The molten anisotropic aromatic polyester of the present invention is composed of repeating structural units derived from, for example, aromatic diols, aromatic dicarboxylic acids, and aromatic hydroxycarboxylic acids. The chemical composition of the structural units derived from aromatic diols, aromatic dicarboxylic acids, and aromatic hydroxycarboxylic acids is not particularly limited, as long as it does not impair the effects of the present invention. Furthermore, within the scope of not impairing the effects of the present invention, the molten anisotropic aromatic polyester may contain structural units derived from aromatic diamines, aromatic hydroxyamines, or aromatic aminocarboxylic acids. For example, the examples shown in Table 1 can be listed as preferred structural units.

[0068] [Table 1]

[0069]

[0070] (Where, X in the formula is selected from the following structure)

[0071]

[0072] (Where, m = 0 to 2, Y = substituents selected from hydrogen, halogen atom, alkyl, aryl, aralkyl, alkoxy, aryloxy, and aralkyloxy)

[0073] In the structural units in Table 1, m is an integer from 0 to 2, and Y in the formula can be independently represented from 1 to the maximum number of substituted atoms, such as hydrogen atoms, halogen atoms (e.g., fluorine atoms, chlorine atoms, bromine atoms, iodine atoms, etc.), alkyl (e.g., methyl, ethyl, isopropyl, tert-butyl, etc., with 1 to 4 carbon atoms), alkoxy (e.g., methoxy, ethoxy, isopropoxy, n-butoxy, etc.), aryl (e.g., phenyl, naphthyl, etc.), aralkyl [benzyl (phenylmethyl), phenethyl (phenylethyl) etc.], aryloxy (e.g., phenoxy, etc.), aralkyloxy (e.g., benzyloxy, etc.), etc.

[0074] As a more preferred structural unit, examples (1) to (18) shown in Tables 2, 3 and 4 below can be cited. It should be noted that when the structural unit in the formula is a structural unit that can represent multiple structures, two or more such structural units can also be combined as structural units constituting the polymer.

[0075] [Table 2]

[0076]

[0077] [Table 3]

[0078]

[0079] [Table 4]

[0080]

[0081] In the structural units of Tables 2, 3, and 4, n is an integer of 1 or 2. Each structural unit n=1 or n=2 can exist alone or in combination. Y1 and Y2 can each independently be a hydrogen atom, a halogen atom (e.g., fluorine atom, chlorine atom, bromine atom, iodine atom, etc.), an alkyl group (e.g., methyl, ethyl, isopropyl, tert-butyl, etc., with 1 to 4 carbon atoms), an alkoxy group (e.g., methoxy, ethoxy, isopropoxy, n-butoxy, etc.), an aryl group (e.g., phenyl, naphthyl, etc.), an aralkyl group [benzyl (phenylmethyl), phenethyl (phenylethyl), etc.], an aryloxy group (e.g., phenoxy, etc.), an aralkyloxy group (e.g., benzyloxy, etc.), etc. Among them, hydrogen atom, chlorine atom, bromine atom, or methyl group are preferred.

[0082] In addition, as Z, substituents represented by the following formula can be cited.

[0083] [Chemical Formula 1]

[0084]

[0085] The melt-forming anisotropic aromatic polyester is preferably a combination having a naphthalene backbone as a structural unit. It should be noted that it is particularly preferred to include both structural units (A) derived from hydroxybenzoic acid (HBA) and structural units (B) derived from hydroxynaphthoic acid (HNA). For example, as structural unit (A), the following formula (A) can be cited, and as structural unit (B), the following formula (B) can be cited. From the viewpoint of improving melt-forming properties, the ratio of structural unit (A) to structural unit (B) is preferably in the range of 9 / 1 to 1 / 1, more preferably 7 / 1 to 1 / 1, and even more preferably in the range of 5 / 1 to 1 / 1.

[0086] [Chemical Formula 2]

[0087]

[0088] [Chemical Formula 3]

[0089]

[0090] Furthermore, the total percentage of structural units (A) and (B) can be, for example, 65 mol% or more, more preferably 70 mol% or more, and even more preferably 80 mol% or more relative to all structural units. In the polymer, it is particularly preferred that the structural units (B) comprise 4 to 45 mol% of a melt-isotropic aromatic polyester.

[0091] The melting point of the molten anisotropic aromatic polyester preferably used in this invention is preferably in the range of 250–360°C, more preferably 260–320°C. The melting point referred to herein is a value measured by a test method based on JIS K7121, and is the peak temperature of the main endothermic peak observed by a differential scanning calorimeter (e.g., Shimadzu Corporation DSC: Differential scanning calorimetry).

[0092] It should be noted that, without impairing the effects of the present invention, the above-mentioned melt anisotropic aromatic polyester may contain thermoplastic polymers such as polyethylene terephthalate, modified polyethylene terephthalate, polyolefins, polycarbonate, polyamide, polyphenylene sulfide, polyetheretherketone, and fluoropolymers. Additionally, it may contain inorganic substances such as titanium dioxide, kaolin, silicon dioxide, and barium oxide, as well as colorants such as carbon black, dyes, and pigments, antioxidants, ultraviolet absorbers, and light stabilizers.

[0093] (Sheath component)

[0094] The sheath component has an island structure, with the flexible thermoplastic polymer (B polymer) forming the sea component and the molten anisotropic aromatic polyester (C polymer) forming the island component.

[0095] Examples of flexible thermoplastic polymers (B polymers) that form marine components include polymers without aromatic rings in their main chain, or polymers with aromatic rings in their main chain and four or more atoms in the main chain between the aromatic rings. Specific examples include: polyolefins; polyamides; polycarbonates; polyphenylene sulfide (PPS); polyethylene terephthalate, modified polyethylene terephthalate, amorphous polyarylates, polyethylene naphthalate (PEN), and other polyesters; polyetheretherketones; and fluoropolymers. These flexible thermoplastic polymers can be used alone or in combination of two or more. One can be used as the main (e.g., accounting for 80% or more by weight) thermoplastic polymer, while others can be added as thermoplastic polymers. PPS and PEN-based thermoplastic polymers are preferred.

[0096] In addition, flexible thermoplastic polymers can contain inorganic substances such as titanium dioxide, silicon dioxide, and barium oxide, as well as various additives such as carbon black, colorants such as dyes or pigments, antioxidants, ultraviolet absorbers, light stabilizers, and nucleating agents.

[0097] The melt-anisotropic aromatic polyester (polymer C) forming the island component can be exemplified by the melt-anisotropic aromatic polyester described in polymer A above. It can be the same as or different from polymer A. From an affinity point of view, a melt-anisotropic aromatic polyester with the same main structural unit is preferred. Furthermore, polymer A and polymer C can be the same type of polymer with the same main structural unit, but differing, for example, only in the addition of thermoplastic polymers or additives.

[0098] In addition, the melting point (Mc) of polymer C can be appropriately selected within a range that allows polymer C to be micro-dispersed in polymer B. For example, relative to the melting point (Mb) of polymer B, the melting point (Mc) of polymer C can be in the range of (Mb-10) to (Mb+80) °C or in the range of Mb to (Mb+70) °C.

[0099] Furthermore, from the viewpoint of spinnability, the melt viscosity η of the C polymer can be, for example, 10 to 60 Pa·s, preferably 20 to 50 Pa·s, and more preferably 25 to 45 Pa·s.

[0100] It should be noted that the melt viscosity η mentioned in this invention refers to the melt viscosity at a temperature T (T = (Mc + 10)℃ when the melting point (Mc) of the C polymer is above 290℃, and T = 300℃ when the melting point Mc is below 290℃) and a shear rate of 1000 sec. -1 The melt viscosity was measured under the specified conditions.

[0101] (Manufacturing method of core-sheath composite fiber)

[0102] The core-sheath composite fiber of the present invention can be manufactured by a manufacturing method that includes at least a mixing process and an extrusion process. The manufacturing process may further include a heat treatment process.

[0103] In the compounding process, a twin-screw extruder is used to melt and compound the aforementioned polymer B and polymer C used in the sheath component, and a different extruder than the twin-screw extruder used in the sheath component is used to melt and compound the polymer A used in the core component.

[0104] In particular, in the twin-screw extruder used for compounding polymers B and C, the set temperature of the compounding section of the twin-screw extruder is set to be (Mb) °C or higher relative to the melting point (Mb) of polymer B and (Mc-20) °C or higher but lower than (Mc) °C relative to the melting point (Mc) of polymer C. By rotating the parallel twin-shaft screws supported in the compounding section in a freely rotatable manner, the micro-dispersion of multiple islands in the sheath component can be achieved.

[0105] It should be noted that the extruder used to melt and compound the aforementioned polymer A used in the core component can be either a single-screw extruder or a twin-screw extruder. Furthermore, when using raw materials prepared by pre-mixing polymers B and C under the aforementioned conditions, since micro-dispersion of the multiple islands in the sheath component can already be achieved, the extruder used for melt compounding the sheath component can be either a single-screw extruder or a twin-screw extruder.

[0106] In the compounding process, from the viewpoint of improving resistance to fibrillation and suppressing the exposure of the core component, the ratio of the core component to the sheath component, expressed as the weight ratio of the core component to the sheath component (hereinafter sometimes simply referred to as the core-sheath ratio), can be, for example, 20 / 80 to 97 / 3, preferably 50 / 50 to 96 / 4, more preferably 60 / 40 to 95 / 5, further preferably 70 / 30 to 94 / 6, even more preferably 75 / 25 to 93 / 7, particularly preferably 80 / 20 to 92 / 8, and most preferably 82.5 / 17.5 to 90 / 10. Especially when the core component is 50% or more, the strength of the composite fiber can be improved, and therefore this is preferred. The weight ratio of the core component to the sheath component can be determined, for example, by calculating the weight ratio of the core component to the sheath component fed into each of the extruders described later during manufacturing.

[0107] The proportion of island components in the sheath component exceeds 10% by weight, preferably 15% by weight or more, and more preferably 20% by weight or more. By increasing the proportion of island components, the fixation effect between the core component and the sheath component brought about by the island components can be strengthened. On the other hand, if the proportion of island components is too high, the possibility of island components agglomeration increases. Therefore, the island components can be 40% by weight or less, preferably 35% by weight or less.

[0108] In the ejection process, the sheath component and core component, which have been separately mixed in the above-mentioned mixing process, can be extracted from, for example... Figure 4 The spinneret of the structure shown combines and ejects the fibers, thereby spinning them into a core-sheath composite fiber with a circular cross-section (fiber cross-section).

[0109] Relative to the melting point (Ma) of polymer A, the spinneret temperature (spinning temperature) at the time of extrusion can be, for example, (Ma+10) to (Ma+60) °C, preferably (Ma+15) to (Ma+40) °C, and more preferably (Ma+20) to (Ma+35) °C.

[0110] The shape of the micro-dispersed islands can be controlled by the draw value. The extruded filaments can be drawn with a draw value of 13 to 50, preferably 15 to 45, more preferably 16 to 40, further preferably 19 to 38, and particularly preferably 20 to 35. It should be noted that the extruded filaments refer to the filaments extruded from the nozzle orifice without being stretched, that is, filaments with a fiber diameter that is substantially the same as the nozzle orifice diameter. In addition, the draw value refers to the ratio of the winding speed to the extrusion speed during spinning.

[0111] The spun fibers can be further heat-treated. Heat treatment can not only improve the orientation crystallinity of the B polymer in the sheath component, but also enable the molten anisotropic aromatic polyester to undergo solid-phase polymerization, thereby improving the strength of the core-sheath composite fiber.

[0112] In heat treatment, the spun fibers can be heat-treated in an inert gas atmosphere such as nitrogen, or in an oxygen-containing active gas atmosphere (e.g., air) under normal or reduced pressure.

[0113] When heat treatment is performed, the heat treatment gas atmosphere is preferably a low-humidity gas with a dew point of -50°C or less, more preferably -60°C or less, and more preferably -70°C or less. As heat treatment conditions, a temperature pattern in which the temperature is increased sequentially from (Ma-20)°C or less, more preferably (Ma-30)°C or less, and more preferably (Ma-40)°C or less relative to the melting point (Ma) of polymer A, to below the melting point of the sheath component.

[0114] Methods of supplying heat include using a gaseous medium, using radiation methods such as heating plates or infrared heaters, and internal heating methods using high frequencies. Processing can be continuous roll-to-roll production or batch production based on skeins or bundles, where the spinning filaments are unwound into heat treatment tubes.

[0115] From the viewpoint of preventing sheath peeling and other issues caused by the adhesion of the heat-treated fibers, inorganic microparticles can be coated onto the surface of the fibers as needed, either during or after spinning and before heat treatment. Preferably, these inorganic microparticles are silicate compounds, such as talc or mica.

[0116] Unlike Patent Document 2, in this invention, even without the attachment of inorganic particles, it has good soothing properties. From the viewpoint of further improving soothing properties, the attachment of inorganic particles can also be performed.

[0117] By uniformly attaching inorganic microparticles to the surface of the fiber during or after spinning and before heat treatment, direct contact between the fibers can be prevented, thus avoiding fiber sticking. It should be noted that most inorganic microparticles, with silicate compounds as the main component, are inactive, and even if they attach to the fiber, no reduction in fiber properties is observed.

[0118] The method for attaching the inorganic particles to the fiber surface is not limited as long as it can achieve uniform adhesion to the fiber. For example, the method of attaching the material obtained by stirring and dispersing the inorganic particles in a spinning oil using an oiling roller or a ruling pen is simple and therefore preferred.

[0119] From the viewpoint of uniform adhesion to the fiber surface, the average particle size of the inorganic particles attached to the surface of the core-sheath composite fiber can be, for example, in the range of 0.01 to 10 μm, preferably 0.02 to 5 μm. The amount of inorganic particles attached to the surface of the core-sheath composite fiber can be in the range of 0.03 to 2.5% by mass, preferably 0.1 to 2.3% by mass.

[0120] (Core-sheath composite fiber)

[0121] Figure 1A This is a three-dimensional schematic diagram of a core-sheath composite fiber according to one embodiment of the present invention. Figure 1B This is a schematic cross-sectional view of the core-sheath composite fiber as observed when it is cut along the fiber length. The core-sheath composite fiber 10 has a core 12 formed of a core component and a sheath 14 formed of a sheath component.

[0122] Figure 2 It is Figure 1B An enlarged cross-sectional view showing a portion of Part II. (See image.) Figure 1B and Figure 2 As shown, in the cross-section (fiber longitudinal section) obtained by cutting the core-sheath composite fiber along the fiber length direction in a manner including its fiber central axis, the sheath portion 14 forms an island structure, and multiple island portions 18 are formed in the sea portion 16. The island portions are slightly dispersed in the sea portion, and the shape of the island portions is controlled.

[0123] In the case of the core-sheath composite fiber of the present invention, since the proportion of island components in the marine component is increased and the islands are micro-dispersed, not only can the adhesion between the sheath and the core be strengthened through multiple islands, thus suppressing sheath peeling, but also the fibrillation of the sheath can be suppressed.

[0124] In the case of microdispersion, the islands are generally elliptical in shape and extend along the fiber length. If the island diameter is large, the unevenness of the fiber surface from the island components becomes greater. Since fibril formation originates from the size of this unevenness on the fiber surface, it is preferable that the maximum diameter of the islands is small. Furthermore, if the islands are elongated along the fiber length, they can provide a better fixation effect, which is also preferable. That is, measuring only the diameter of the islands in a single fiber cross-section does not account for the contribution of the fixation effect caused by the length of the islands. However, by observing the shape of the islands along the length direction in a microscopic photograph of the sheath, and considering both the width and length of the island with the maximum width, the shape of the island can be evaluated. This allows for the evaluation of fibrilability while taking into account the contribution of the fixation effect of the islands. Therefore, after selecting an island with the maximum width W, for that island, if... Figure 2 As shown, the maximum length L1 of the oblique length, which coincides with the length of the oblique line extending at an angle α (10°) determined relative to the fiber length direction, is measured from one end of the fiber length direction to the other. L1 / W is then calculated, thereby enabling the evaluation of the shape of the island portion that takes into account the elongation in the fiber length direction.

[0125] First, the island with the maximum width W can be selected from the magnified image of the fiber longitudinal section. Specifically, using a scanning probe microscope (SPM) described later, the fiber longitudinal section is observed along the fiber length direction at a distance of 100 μm to 1000 μm. Within this observation range, the value of the portion of the island whose length in the direction perpendicular to the fiber length direction (fiber perpendicular direction) is the maximum is taken as the measured value. The observation range does not need to be continuous; it can be the sum of multiple randomly extracted fields of view. For example, within the observation range of the fiber longitudinal section, from multiple islands extending along the fiber length direction, multiple islands with relatively large lengths in the fiber perpendicular direction are extracted. The fiber perpendicular length of the extracted islands is compared as the width of the island, thereby determining the island with the maximum width. In this example, in the fiber longitudinal section, only a portion of the upper and lower parts of the sheath component (e.g., Figure 1BThe lower part of the fiber can be used as the observation area. In this example, the maximum width of the island was determined by observing the longitudinal section of the fiber using a scanning probe microscope. However, any method other than scanning probe microscopy can be used if the maximum width of the island can be determined. It should be noted that, to minimize the impact of stress during fiber cutting, it is preferable to cut the fiber after it has been fixed by resin embedding.

[0126] The maximum width W of the island portion is 0.65 μm or less, preferably 0.60 μm or less, more preferably 0.55 μm, and even more preferably 0.50 μm or less. When the maximum width of the island portion exceeds the above-mentioned upper limit, there is a risk that the resistance to fibrils may become insufficient. In addition, the maximum width W of the island portion can be 0.07 μm or more, or 0.1 μm or more.

[0127] After selecting the island with the maximum width W, observe the island continuously along its length, such as... Figure 2 As shown, the maximum length L1 of the oblique length, which coincides with the length of an oblique line extending at an angle α (10°) determined relative to the fiber length direction, is measured from one end of the fiber length direction towards the other. When the ratio L1 / W of the maximum oblique length to the maximum width W is 5.0 or more, the core-sheath composite fiber can suppress fibrillation and improve the fixation effect brought about by the island portion. The L1 / W is preferably 5.1 or more, more preferably 5.2 or more, further preferably 5.3 or more, and even more preferably 5.5 or more. There is no particular limitation on the upper limit of L1 / W, which can be 10 or less.

[0128] The maximum length L1 of the aforementioned oblique length is a value that varies correspondingly to the maximum width W. For example, it can be 1.0 μm or more, preferably 1.3 μm or more, more preferably 1.5 μm or more, and even more preferably 1.7 μm or more. When the maximum length L1 of the oblique length is above the aforementioned lower limit value, there is a tendency for the fixation effect on the core component to increase. In addition, the maximum length L1 of the aforementioned oblique length can be 3.3 μm or less, preferably 3.1 μm or less, and more preferably 2.9 μm or less. When the maximum length L1 of the oblique length is below the aforementioned upper limit value, there is a tendency for fibrillation to be suppressed.

[0129] In the aforementioned fiber longitudinal section, the length L2 of the island portion with the largest width in the sheath component, along its fiber length direction, can be, for example, 450–1000 μm, preferably 500–800 μm, and more preferably 550–650 μm. A longer L2 improves the fixation effect on the core component. The length of this island portion along its fiber length direction can be determined from a magnified image of the fiber longitudinal section. Alternatively, the length of the island portion along its fiber length direction can be determined by the yarn output, and calculated as a value obtained by multiplying this value by the draw value.

[0130] From the viewpoint of preventing the core component from being exposed and ensuring the strength of the fiber, the thickness of the sheath component can be, for example, 0.8 to 5.0 μm, preferably 0.9 to 4.0 μm, and more preferably 0.9 to 3.8 μm.

[0131] like Figure 3 As shown, the thickness of the sheath component can be determined, for example, by examining a magnified image of the cross-section observed when the core-sheath composite fiber is cut along a plane perpendicular to the fiber length direction (hereinafter, sometimes referred to as the "fiber cross-section"). Specifically, the fiber cross-section can be photographed using a scanning microscope or similar means, and the radial distance from the outer circumferential surface of the core component to the outer circumferential surface of the sheath component can be measured at any three points that divide the outer circumference of the fiber into three equal parts. The thickness of the sheath component can then be determined based on the average value of these distances. It should be noted that, to minimize the effects of stress during fiber cutting, it is preferable to embed the fiber in resin to fix it before cutting.

[0132] The monofilament fineness of the core-sheath composite fiber can be, for example, 1–120 dtex, preferably 2–60 dtex, more preferably 2.5–30 dtex, and even more preferably 3–15 dtex. This monofilament fineness can be determined, for example, based on JIS L 1013 "Test Method for Chemical Fiber Filaments". Furthermore, the core-sheath composite fiber can be a monofilament yarn or a multifilament comprising two or more monofilament yarns.

[0133] The tensile strength of the core-sheath composite fiber in a gaseous atmosphere at 25°C can be, for example, 10 cN / dtex or higher, preferably 13 cN / dtex or higher, more preferably 15 cN / dtex or higher, even more preferably 18 cN / dtex or higher, and even more preferably 20 cN / dtex or higher. There is no particular upper limit to the tensile strength, and it can be 30 cN / dtex or lower. Here, the tensile strength is a value measured with reference to the JIS L 1013 test method. It should be noted that when the core-sheath composite fiber is a multifilament, considering the change in strength caused by fiber alignment, one fiber can be extracted from the multifilament and measured as a single filament tensile strength.

[0134] The core-sheath composite fiber exhibits excellent resistance to fibrils. For this core-sheath composite fiber, the test fiber was passed through three comb-shaped guides arranged at 120° angles, and a load of 1 g / dtex was applied to each fiber. Under conditions of a stroke length of 3 cm and a speed of 95 cycles / min, and 30,000 reciprocating motions were performed, the average number of burrs per 3 cm fiber length (average over 5 cycles) was, for example, less than 1, and preferably less than 0.5. Here, when the core-sheath composite fiber was magnified 20 times using a camera, small burrs (fibrils) less than 1 mm, burrs greater than 1 mm, and sheath peeling could be observed.

[0135] The core-sheath composite fiber of the present invention can be woven and braided using conventional methods. Furthermore, it can be dyed using conventional methods depending on the type of flexible thermoplastic polymer. For example, if the flexible polymer is a polyester polymer, it can be dyed using conventional polyester fiber dyeing methods that utilize disperse dyes.

[0136] The core-sheath composite fiber of the present invention can be suitably used as various fiber structures, and the fiber structure of the present invention comprises at least a portion of the core-sheath composite fiber of the present invention. Examples of fiber structures include one-dimensional structures such as ropes and blended filaments, and two-dimensional structures such as fabrics, knitted fabrics, and nonwoven fabrics, as well as other advanced processed products. The fiber structure can be composed solely of the core-sheath composite fiber, or it can include other constituent components without compromising the effects of the present invention. After the fiber structure is temporarily formed, it can be dyed using the dyeing method described above.

[0137] When the fibrous structure is a fabric, there are no particular limitations on the fabric structure. Examples include plain weave, twill weave, satin weave, varied plain weave, varied twill weave, varied satin weave, fancy weave, jacquard weave, single-layer weave, double-layer weave, multi-layer weave, warp pile weave, weft pile weave, and leno weave. Similarly, when the fibrous structure is a knitted fabric, there are no particular limitations on the knitted fabric structure. Examples include circular knit, weft knit, warp knit (including Trico warp knit and Raschel warp knit), terry knit, plain knit, knitted weave, rib weave, double rib weave (two-sided knit), rib knit, double reverse weave, warp plain weave, warp pile weave, warp knit satin weave, chain weave, and interlining weave.

[0138] Example

[0139] The present invention will now be described in more detail through examples, but the invention is not limited to these examples in any way. It should be noted that in the following examples and comparative examples, various physical properties were measured using the methods described below.

[0140] [Fineness]

[0141] Based on JIS L 1013:2010 8.3.1A, using a measuring instrument manufactured by Daiei Scientific Precision Instruments, 100m of core-sheath composite fiber was wound onto a spool, and its weight (g) was multiplied by 100. Three measurements were performed for each level, and the average of the three measurements was taken as the fineness (dtex).

[0142] Tensile strength

[0143] Based on JIS L 1013, a USTER TENSORAPID5 tensile strength and elongation tester was used. Under conditions of a test length of 20 cm, a tensile speed of 10 cm / min, and an initial load of 0.33 g / dtex, five measurements were performed on each sample. The average of the five measurements was taken as the strength (cN / dtex). It should be noted that when the core-sheath composite fiber was a multifilament, one filament was taken from the multifilament, and the tensile strength of the single filament was measured.

[0144] [Thickness of the sheath component]

[0145] The core-sheath composite fiber was embedded in epoxy resin, and the embedded material was cut in a plane perpendicular to the fiber length direction, thereby creating a cross-section of the fiber. In this fiber cross-section, the radial distance from the outer circumference of the core to the outer circumference of the sheath was measured at any three points dividing the outer circumference of the fiber into three equal parts using a microscope, and the average value was calculated as the thickness of the sheath component.

[0146] [Island length, maximum island width]

[0147] Core-sheath composite fibers were embedded in epoxy resin, and the embedded material was cut along the fiber length using a cross-sectional polisher (CP) to create a longitudinal section of the fiber. The fiber longitudinal section was then observed using a scanning probe microscope (SPM) at a distance of 100 μm to 1000 μm along the fiber length. Within the observation range, several islands with relatively large vertical lengths were extracted from multiple islands extending along the fiber length. The vertical length of the extracted islands was used as the width of the islands, and comparisons were made. The maximum width W of the island with the largest width was determined. Furthermore, the fiber length L2 was measured for the island with the largest width W.

[0148] [Maximum length of the island's diagonal section]

[0149] Next, for the island with the maximum width W, from one end of the fiber length direction to the other, measure the longest line segment that coincides with the oblique line extending at an angle α (10°) determined relative to the fiber length direction, and take it as the maximum length L1 of the oblique length of the island.

[0150] [Abrasion Resistance]

[0151] Using a TM-200 cohesion testing machine manufactured by Daiei Scientific Instruments Co., Ltd., the fibers of the test subject were passed through three comb-shaped guides arranged at 120° angles, with each fiber subjected to a load of 1 g / dtex. The test was performed 30,000 reciprocating motions at a stroke length of 3 cm and a speed of 95 cycles / min. The condition of the burrs was confirmed by magnification up to 20x using a camera. This test was repeated five times, observing the presence or absence of burrs for every 3 cm of fiber length. It should be noted that the generated burrs were distinguished into microburrs less than 1 mm in length and burrs longer than 1 mm, and were evaluated according to the following criteria.

[0152] (Whether or not burrs are produced)

[0153] ◎: No burrs were observed in any of the 5 tests.

[0154] ○: Burrs were observed in more than one of the five tests, but no burrs longer than 1 mm were observed in any of them.

[0155] ×: For cases where burrs were observed more than once in 5 trials, and burrs longer than 1 mm were observed more than once.

[0156] In addition, for cases where burrs were observed to occur more than once in 5 tests, the number of burrs produced was measured and calculated as the average of the 5 tests mentioned above.

[0157] [Example 1]

[0158] Core-sheath composite fibers were manufactured using the following method.

[0159] In the core component, a melt-anisotropic aromatic polyester [melting point (Ma): 278℃, melt viscosity (MVa): 32.1 Pa·s] with a molar ratio of structural units (P: HBA) to (Q: HNA) of 73 / 27 was used as polymer A. In the sheath component, PEN [melting point (Mb): 266.3℃, melt viscosity (MVb): 100 Pa·s] was used as polymer B to form the island component, and the same melt-anisotropic aromatic polyester [melting point (Mc): 278℃, melt viscosity (MVc): 32.1 Pa·s] as polymer A was used as polymer C to form the island component.

[0160] In the compounding process, the core and sheath components are melt-blended using their respective extruders. In the sheath component compounding process, polymers B and C are mixed to achieve a core-to-sheath ratio of 30% by weight. After the compounding extrusion begins, the set temperature of the compounding section of the twin-screw extruder is set to 266°C ((Mc-12)°C), and after thorough compounding (low-temperature compounding process), in the extrusion process, the sheath component ratio is controlled to 0.35 (65 / 35 by weight, based on the core-to-sheath ratio). Figure 4 Using a spinneret with a specific structure, spinning was performed at a spinning temperature of 310℃ and a draw ratio of 22.3 times, resulting in a core-sheath composite fiber with a monofilament yarn of 10.3 dtex. The fiber exhibited good spinnability and could be collected without breaking the yarn.

[0161] Next, as a heat treatment process, the obtained fibers were unwound into a heat treatment tube, and the treatment temperature was gradually increased, with the maximum temperature set at 260°C, and carried out for 18 hours in a nitrogen atmosphere. The unwinding properties of the heat treatment tube were satisfactory, and the obtained heat-treated filaments exhibited the properties shown in Table 5.

[0162] [Examples 2-8]

[0163] The core-sheath ratio, the proportion of island components in the sheath, the number of filaments, the fineness of the monofilaments, and the draw value were varied as shown in Table 5. Otherwise, the core-sheath composite fibers were manufactured in the same manner as in Example 1. The results are shown in Table 5. Spinability was good in all cases, and collection could be carried out without filament breakage.

[0164] [Comparative Example 1]

[0165] The chips of polymers B and C, representing the sheath component, were manually mixed. Using the resulting chip mixture, polymers B and C were further mixed to achieve a sheath component ratio of 30% by weight. In a cryogenic compounding process, melt compounding was performed at 310°C using a single-screw extruder. This resulted in a sheath component ratio controlled at 0.35 (65 / 35 by weight, based on a core-to-sheath ratio). Figure 4 The spinneret with the structure was used for spinning at a spinning temperature of 310°C and a draw ratio of 9.9. Except for this, spinning and heat treatment were performed in the same manner as in Example 1 to manufacture core-sheath composite fibers. The spinnability was poor, and filament breakage occurred. The results are shown in Table 5.

[0166] [Comparative Example 2]

[0167] The core-sheath composite fiber was manufactured in the same manner as Comparative Example 1, except that the island component in the sheath component was mixed to achieve a proportion of 20% by weight. Poor spinnability resulted in filament breakage. The results are shown in Table 5.

[0168] [Comparative Example 3]

[0169] The core-sheath composite fiber was manufactured by mixing in such a way that the proportion of island components in the sheath component reached 5% by weight, and then spinning and heat treatment were performed in the same manner as in Comparative Example 1. As described in Patent Document 1, since the proportion of island components in the sheath component was 10% by weight or less, the spinning properties were good, and it was possible to collect the fiber without breaking the filament. The results are shown in Table 5.

[0170] [Comparative Example 4]

[0171] Core-sheath composite fibers were manufactured in the same manner as Comparative Example 1, with a sheath component ratio of 0.15 (a core-sheath ratio (by weight) of 85 / 15) and a draw value of 15.5. Spinning properties were poor, and filament breakage occurred. The results are shown in Table 5.

[0172] [Comparative Example 5]

[0173] In the compounding process of the sheath component, the same low-temperature compounding process as in Example 1 was performed. Except for this, spinning and heat treatment were performed in the same manner as in Comparative Example 1 to produce core-sheath composite fibers. The fibers exhibited good spinnability and could be collected without filament breakage. The results are shown in Table 5.

[0174]

[0175] As shown in Table 5, in Examples 1 to 8, even though the proportion of melt anisotropic aromatic polyester in the sheath component was increased, high abrasion resistance and spinnability could be achieved by controlling the shape of the island portion of the island structure of the sheath component.

[0176] In Examples 1-8, no burrs larger than 1 mm were observed in the wear test based on 30,000 reciprocating motions, and therefore, sheath peeling did not occur, demonstrating excellent wear resistance. Particularly in Examples 2-3, even microfibers smaller than 1 mm were not observed, possibly due to the small maximum width of the island. Furthermore, in Examples 1 and 4-5, although the maximum width of the island was greater than in Examples 2-3, it is possible that by reducing the width and increasing the length of the island, the maximum length L1 / maximum width W of the island's oblique direction could be increased. Therefore, even microfibers smaller than 1 mm were not observed, or were observed only once out of five measurements.

[0177] In particular, in Examples 4 and 5, by controlling the shape of the islands in the sheath composition, wear resistance can be maintained even when the sheath is thinned, and the strength is also increased due to the high core composition ratio.

[0178] Furthermore, in both Example 6 with small monofilament fineness and Examples 7-8 with large monofilament fineness, better wear resistance was observed than in Comparative Examples 1-3 by controlling the island shape in the sheath component.

[0179] On the other hand, Comparative Example 1, due to the lack of a specific melt-blending process for the sheath component, exhibited poor spinnability and experienced fiber breakage during spinning. Furthermore, although Comparative Example 1 had the same core-sheath ratio and island component proportion in the sheath component as Example 1, the maximum width of the island portion in the sheath of the resulting core-sheath composite fiber was greater than that of Example 1, indicating a large island portion. Moreover, possibly due to the small maximum length / maximum width of the island portion's oblique length, the sheath component's fixation effect was not fully utilized. In the burr evaluation during the abrasion resistance test, not only were small burrs (fibrils) less than 1 mm produced, but the number of burrs was also greater than in Example 1. Additionally, burrs larger than 1 mm were produced, resulting in sheath peeling. Furthermore, the fiber strength also showed a lower value than in Example 1.

[0180] In Comparative Example 2, although it had the same core-to-sheath ratio and island component proportion in the sheath composition as Example 2, the maximum width of the islands was larger than in Example 2 because the sheath composition was not subjected to a specific melt-blending process, indicating a large island portion. In the evaluation of burrs during the abrasion resistance test, a greater number of burrs than in Example 2 were also observed, and burrs larger than 1 mm were also generated, indicating sheath peeling. Furthermore, the fiber strength was also lower than in Example 2.

[0181] In Comparative Example 3, although the proportion of melt-isotropic aromatic polyester in the sheath composition was lower than in Examples 1 and 2, the maximum island width was larger compared to Examples 1 and 2, indicating a large island. In the evaluation of burrs during the abrasion resistance test, a greater number of burrs were produced than in Examples 1 and 2; furthermore, burrs larger than 1 mm were produced, indicating sheath peeling. Additionally, the fiber strength was also lower than in Examples 1 and 2.

[0182] In Comparative Example 4, although the core-to-sheath ratio and the proportion of island components in the sheath composition were the same as in Example 5, the maximum length / maximum width of the island portion was small because a specific melt-mixing process was not performed on the sheath composition. As a result, burrs larger than 1 mm were generated, and sheath peeling occurred.

[0183] In Comparative Example 5, since the core-sheath ratio and the proportion of island components in the sheath component were the same as in Example 1, and a specific melt-blending process was performed on the sheath component, the maximum width of the island component was small. However, due to the small draw value during spinning, the maximum length / maximum width of the island portion was small, resulting in burrs greater than 1 mm and sheath peeling occurred.

[0184] Industrial applicability

[0185] For the core-sheath composite fiber of the present invention, since high strength / high elastic modulus and fibrillation can be maintained and suppressed by increasing the proportion of molten anisotropic aromatic polyester in the sheath component, it can be fully applied to tensile components (wires, optical fibers, umbilical cables, heating wire cored yarn, wires for various electronic products such as headphones, etc.), tarpaulins, ropes (marine, mountaineering, crane, yacht, tugboat, etc.), climbing ropes, sports nets, slings, lifelines, fishing lines, sewing threads, window screens, fishing nets, rope hooks, geogrids, protective gloves, ripstop fabrics for protective clothing / outdoor clothing, cycling apparel, sports rackets, catgut, reinforcing materials for medical catheters, sutures, mesh yarn, filters, base fabrics for printed circuit boards, mesh conveyor belts, papermaking belts, canvas for dryers, spacecraft, balloons, airbags, loudspeakers, reinforcing materials for various hoses / catheters, reinforcing materials for rubber / plastics such as tires / conveyor belts, and other advanced processed products. In addition, since it can be dyed using common methods, it is particularly suitable for high-end processed products such as tarpaulins, climbing ropes, sports nets, fishing lines, fishing nets, rope hooks, ripstop fabrics for protective clothing / outdoor clothing, reinforcing materials for rubber / plastics, and general clothing.

[0186] As described above, with reference to the accompanying drawings and preferred embodiments of the invention, those skilled in the art will readily conceive of various changes and modifications within the obvious scope upon reading this specification. Therefore, such changes and modifications are interpreted as falling within the scope of the invention as defined by the claims.

Claims

1. A core-sheath composite fiber, wherein the core component comprises a polymer A as a molten anisotropic aromatic polyester, and the sheath component comprises a polymer B as a flexible thermoplastic polymer and a polymer C as a molten anisotropic aromatic polyester, the sheath component having an island structure in which the polymer B forms a sea element, the polymer C forms an island element, and a plurality of islands formed by the island element are dispersed in a sea element formed by the sea element, wherein... The proportion of island components in the sheath component exceeds 10% by weight, and In the cross-section obtained by cutting the core-sheath composite fiber along its length, the maximum width W of the island portion is less than 0.65 μm. In the island portion having the maximum width W, in the island portion that connects to the oblique line in the sheath component extending at an angle of 10° relative to the fiber length direction from one end to the other, the ratio of the maximum length of the oblique length L1 coinciding with the oblique line to the maximum width W of the island portion L1 / W is 5.0 or more.

2. The core-sheath composite fiber according to claim 1, wherein, The maximum length L1 of the oblique length is 1.0 μm or more.

3. The core-sheath composite fiber according to claim 1 or 2, wherein, In the cross-section obtained by cutting the core-sheath composite fiber along the fiber length direction, the length L2 of the island portion in the sheath component along the fiber length direction is 450~1000μm.

4. The core-sheath composite fiber according to claim 1 or 2, wherein, The thickness of the sheath component is 0.8~5.0 μm.

5. The core-sheath composite fiber according to claim 1 or 2, wherein, Polymer A and polymer C are composed of melt-isotropic aromatic polyesters with the same main structural unit.

6. The core-sheath composite fiber according to claim 1 or 2, wherein, The core component / sheath component ratio is 20 / 80~97 / 3, where the core component / sheath component is the weight ratio of the core component to the sheath component.

7. The core-sheath composite fiber according to claim 1 or 2, wherein, The single filament fineness of this core-sheath composite fiber is 1~120 dtex.

8. A method for manufacturing a core-sheath composite fiber, wherein the core component of the core-sheath composite fiber comprises a polymer A as a melt-anisotropic aromatic polyester, the sheath component comprises a polymer B as a flexible thermoplastic polymer and a polymer C as a melt-anisotropic aromatic polyester, the sheath component having an island structure in which the polymer B forms a sea element, the polymer C forms an island element, and a plurality of islands formed by the island element are dispersed in a sea element formed by the sea element. This method must at least have: In the compounding process, a twin-screw extruder is used to compound the B polymer and C polymer used in the sheath component at a melting point (Mb)°C or higher than the melting point (Mc)°C of the B polymer and a melting point (Mc)°C or higher than the melting point (Mc)°C of the C polymer but lower than the melting point (Mc)°C. In addition, a different extruder than the twin-screw extruder used in the sheath component is used to melt and compound the A polymer used in the core component. In the extrusion process, the sheath and core components, which have been mixed separately in the mixing process, are combined and extruded to obtain the discharged filament; as well as In the extraction process, the extruded filaments are extracted at a ratio of 13 to 50 based on the draw value, where the draw value is the ratio of the winding speed to the extrusion speed.

9. The method for manufacturing the core-sheath composite fiber according to claim 8, wherein the method comprises: The heat treatment process involves heat-treating the fibers obtained through the ejection process.

10. A fiber structure comprising, in at least a portion, the core-sheath composite fiber as described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Conjugate fiber and its woven fabric

    JP2002020932A

  • High-tenacity conjugated fiber and method for producing the same

    JP2008255535A

  • High-frequency coil component, coil component for wireless power supply, wireless power supply device, and manufacturing method of frequency coil component

    JP2021034707A

  • Conjugate fiber for screen gauze and screen gauze

    JP1996260249A

  • Core-sheath conjugate fiber

    JP2007126760A